Role of vibroacoustic stimulation test in prediction of fetal outcome in terms of Apgar score - Singh, Kalpana; Das, Chankya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Role of vibroacoustic stimulation test in prediction of fetal outcome in terms of Apgar score. Aim: To know the efficacy of vibroacoustic stimulation test in prediction of fetal outcome. Methods: The study was conducted in department of obstetrics and gynecology at Guwahati Medical College, in duration of 2007-2009. Total 200 high risk patients underwent VAST. Results: VAST done among all these patients and according to fetal response divided into VAST reactive and non-reactive. In 162 (81%) patients VAST was reactive and 38 (19%) non-reactive. Among VAST (162) reactive patients, 126 (77.77%) went for spontaneous vaginal delivery and for 36 (22.22%) induction planned. Induction failed in 9 patients and cesarean section done. Total babies shifted to NICU 13 (6.5%), 4 babies expired (2%) and 9 (4.5%) improved. Thus VAST has good correlation in prediction of fetal outcome. Conclusions: It is simple, rapid and non-invasive tool for detection of fetal well-being. It is efficacious in detection of early fetal jeopardy as correlated with Apgar score. There are currently no randomized controlled trials that address the safety and efficacy of VAST used to assess fetal well-being.